Artificial intelligence versus expert endoscopists for diagnosis of gastric cancer in patients who have undergone upper gastrointestinal endoscopy - Niikura, Ryota; Aoki, Tomonori; Shichijo, Satoki; Yamada, Atsuo; Kawahara, Takuya; Kato, Yusuke; Hirata, Yoshihiro; Hayakawa, Yoku; Suzuki, Nobumi; Ochi, Masanori; Hirasawa, Toshiaki; Tada, Tomohiro; Kawai, Takashi; Koike, Kazuhiko (Endoscopy, 2022)
Aims To compare endoscopy gastric cancer images diagnosis rate between artificial intelligence (AI) and expert endoscopists.Patients and methods We used the retrospective data of 500 patients, including 100 with gastric cancer, matched 1:1 to diagnosis by AI or expert endoscopists. We retrospectively evaluated the noninferiority (prespecified margin 5 %) of the per-patient rate of gastric cancer diagnosis by AI and compared the per-image rate of gastric cancer diagnosis.Results Gastric cancer was diagnosed in 49 of 49 patients (100 %) in the AI group and 48 of 51 patients (94.12 %) in the expert endoscopist group (difference 5.88, 95 % confidence interval: −0.58 to 12.3). The per-image rate of gastric cancer diagnosis was higher in the AI group (99.87 %, 747 /748 images) than in the expert endoscopist group (88.17 %, 693 /786 images) (difference 11.7 %).Conclusions Noninferiority of the rate of gastric cancer diagnosis by AI was demonstrated but superiority was not demonstrated.